Buoyancy and gravity power generator - Varnamkhasti, Ali Karami (2014)
The present invention discloses an apparatus (100) for generating electrical power from a combination of gravity force and buoyancy of a hollow body immersed in a liquid, which comprises: a first buoyancy chamber (108) and a second buoyancy chamber (106) separated by a bottom partition (112) extending horizontally across the apparatus (100), the first and second buoyancy chambers (108, 106) filled with liquid (114); a gravity chamber (104) separated from the buoyancy chambers (108, 106), a first gate (116) which opens or closes an opening that separates the first buoyancy chamber (108) and second buoyancy chamber (106), and a second gate (118) which opens or closes an opening that separates the gravity chamber (104) and first buoyancy chamber (108); a continuous carrier (124) that entrains about and moves around means (131a-b, 130a-c); and a plurality of hollow floats (122) spaced along the length of the continuous carrier (124). Also disclosed herein is a power generation system (400) comprising a tandem setting of a series of inter-connected apparatus (100).